Hubungan antara Status Gizi dengan Gingivitis pada Mahasiswa Program Studi Pendidikan Dokter Gigi Universitas Sam Ratulangi - Hanifah, Fenti; Kawengian, Shirley E.S.; Tambunan, Elita (Universitas Sam Ratulangi, 2018)
Abstract: Gingivitis is an inflammation process of gingiva caused by accumulation of biofilm on plaques around the margin of gingiva as well as an inflammation response against bacteria. Nutritional status is affected by macro and micronutrient intake. Poor nutritional status can cause abnormality of function and structure of oral soft tissue resulting in increased plaque forming which leads to the occurence of gingivitis. This study was aimed to obtain the relationship between nutritional status and the occurence of gingivitis. This was an analytical study using a cross-sectional design. Samples were obtained by using total sampling method. There were 77 students as samples. The nutritional status was measured by using body mass index (BMI), and examination of oral cavity was performed to check the occurence of gingivitis. The result showed that 46.8% of students had gingivitis. The nutritional status of the students based on IMT were as follows: 19.5% were categorized as underweight, 65% as normal weight, 9% as overweight, and 6.5% as obese. The bivariate analysis using the Chi-square test showed a P value of 0.000 (<0.05). Conclusion: There was a significant relationship between the nutritional status and gingivitis in students of Dentistry Program, Sam Ratulangi University.Keywords: nutritional status, gingivitisÂ Abstrak: Gingivitis merupakan reaksi inflamasi dari gingiva yang disebabkan oleh akumulasi biofilm pada plak di sekitar margin gingiva dan respon peradangan terhadap bakteri. Status gizi dipengaruhi oleh asupan gizi makronutrien dan mikronutrien yang seimbang. Gizi kurang dapat menyebabkan gangguan fungsi dan struktur jaringan lunak mulut sehingga pembentukan plak meningkat yang menjadi penyebab awal gingivitis. Penelitian ini betujuan untuk mengetahui hubungan antara status gizi dengan gingivitis. Jenis penelitian ialah analitik dengan desain potong lintang. Pengambilan sampel menggunakan total populasi sebanyak 77 mahasiswa Program Studi Pendidikan Dokter Gigi Universitas Sam Ratulangi. Status gizi diukur menggunakan rumus perhitungan IMT dan pemeriksaan rongga mulut dilakukan untuk melihat ada tidaknya gingivitis. Hasil penelitian menunjukkan 46,8% mahasiswa mengalami gingivitis. Penentuan status gizi berdasarkan IMT mendapatkan sampel kategori kurus (19,5%), normal (65%), berat badan lebih (9%), dan obesitas (6,5%). Hasil analisis bivariat menggunakan uji Chi-square menunjukkan nilai P = 0,000 (0,000 <0,05). Simpulan: Terdapat hubungan bermakna antara status gizi dengan gingivitis pada mahasiswa Program Studi Pendidikan Dokter Gigi Universitas Sam Ratulangi.Kata kunci: status gizi, gingivitis